A clash on the Toll pathway: competitive action between pesticides and zymosan A on components of innate immunity in Apis mellifera - Sukkar, Dani; Kanso, Ali; Laval-Gilly, Philippe; Falla-Angel, Jairo (Frontiers in Immunology, 2023)
The immune system of honeybees includes multiple pathways that may be affected by pesticide exposure decreasing the immune competencies of bees and increasing their susceptibility to diseases like the fungal Nosema spp infection, which is detected in collapsed colonies. To better understand the effect of the co-presence of multiple pesticides that interact with bees like imidacloprid and amitraz, we evaluated the expression of immune-related genes in honeybee hemocytes. Our results revealed that imidacloprid, amitraz, and the immune activator, zymosan A, mainly affect the Toll pathway and they have a synergistic or an antagonistic relationship on gene expression depending on the level of immune signaling. The presence of multiple risk factors like pesticides and pathogens obligates the assessment of their complex interaction that have differential effects on the innate immunity of honeybees as seen in this study.